(3TQM UMjM GdHNGQi e TQM GdLGeY GdUMjMs - (3CHh dSjeGf MeO Hf eMeO GdNWGHis; (3eSde Hf GdMLGL Hf eSde GdbTjQj GdfjSGHhQqi, CHh GdMSjf,J (B261 (3g` s ((3OeT GdeMQhSI s)
(3ChdgG (B:s
(3bGd CHh SdjeGf SeYJ QShd Gddg Udi Gddg Ydjg hSde jbhd GfeG GdCYeGd HGdfjGJ GdMOjK s
(3BNQgG (B:s
(3GJHGYkG dePgHg hMaXkG dQSeg BNQ cJGH GdCYdGe s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B221 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B232s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdMOjK h GdeUWdMs